2011
DOI: 10.1111/j.1745-459x.2011.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes and Expectations of Ginseng Food Products Assessed by Focus Groups and Conjoint Analysis

Abstract: Ginseng food products in the U.S.A. have mostly been limited to beverages despite the growth of functional foods market. The objectives of the study were to: (1) probe consumer attitudes and expectations of ginseng food products in the U.S.A., and (2) identify ginseng food product concept(s) that possess market potential in the U.S.A. Focus group panel (n = 14) experienced limited types of ginseng food products from the Asian market and suggested that new ginseng food products be developed on the basis of pree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 42 publications
5
43
2
4
Order By: Relevance
“…A study about ginseng products revealed consumers' knowledge and insights of ginseng and its health effects (Chung, Hong, Kim, Cho, Moskowitz & Lee, 2011). This coincides with the findings of this article, since consumers were very aware of pigeon pea's health benefits and considered making new products from this legume was beneficial and had great potential, which this article also found.…”
Section: Discussionsupporting
confidence: 75%
“…A study about ginseng products revealed consumers' knowledge and insights of ginseng and its health effects (Chung, Hong, Kim, Cho, Moskowitz & Lee, 2011). This coincides with the findings of this article, since consumers were very aware of pigeon pea's health benefits and considered making new products from this legume was beneficial and had great potential, which this article also found.…”
Section: Discussionsupporting
confidence: 75%
“…One composed by seven participants with previous experience on sensory analysis of DFS (3 males, 4 females; 25 to 58 years) and other composed by six participants with no experience on sensory analysis (2 males, 4 females; 28 to 62 years). The moderator facilitated the discussion according to previously planned guidelines (Table 3) (Chung, Hong, Kim, Cho, & Moskowitz, 2011). Samples were presented in the discussion by the experimental design order.…”
Section: Sensorial Evaluationmentioning
confidence: 99%
“…The study subject was first presented with a welcome screen followed by 60 permutations of the element groupings, each with a rating question, with every element appearing exactly 5 times in randomized combinations ( Figure 1). The combinations of elements were randomized across participants, as was the order in which the concepts were presented [15]. To mitigate participant fatigue all 60 randomized combinations were unique but the elements were repeated so the participant was not required to imagine novel elements in all 60 concepts.…”
Section: Basic Experimental Procedures and Participant Recruitmentmentioning
confidence: 99%